Strength and chloride ion penetration resistance of ultra-high-performance fiber reinforced geopolymer concrete. (August 2021) - Mousavinejad, Seyed Hosein Ghasemzadeh; Sammak, Moein
Abstract: Using high amount of cement is one of the disadvantages of ultra-high-performance concrete (UHPC). To reduce this, it is tried to replace cement with certain alternative materials with industrial waste materials and disposal. In this research, Ultra-high-performance geopolymer concrete (UHPGC) based on ground granulated blast furnace slag (GGBFS) and silica fume containing steel fiber (SF) and polypropylene fiber (PPF) was investigated experimentally. For this purpose, series 1 of mix proportion has been used to determine the reference design with the highest compressive strength. In series 2, nine mixtures were used to investigate the effect of fibers on mechanical properties of the UHPGC including compressive strength, splitting tensile strength, flexural strength and also modulus of elasticity. Moreover, the chloride ion penetration resistance was evaluated through some specific tests such as electrical resistivity (ER), rapid chloride migration test (RCMT) and rapid chloride penetration test (RCPT). The results show that addition of PPF to the samples containing SF improves the mechanical and durability properties. Moreover, the results indicate that replacing the percentage of SF with PPF leads to reduction in the mechanical strength, although it causes the durability to be increased.